2023
DOI: 10.1109/jsyst.2022.3170406
|View full text |Cite
|
Sign up to set email alerts
|

An Anonymous IoT-Based E-Health Monitoring System Using Blockchain Technology

Abstract: The Internet of things (IoT) has made it possible for health institutions to have remote diagnosis, reliable, preventive and real-time decision making. However, the anonymity and privacy of patients are not considered in IoT. Therefore, this paper proposes a blockchain-based anonymous system, known as GarliMediChain, for providing anonymity and privacy during COVID-19 information sharing. In GarliMediChain, garlic routing and blockchain are integrated to provide low-latency communication, privacy, anonymity, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The primary information of the included papers [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ] is shown in Table 1 . Based on the data shown in Figure 4 , we can observe that 13.95% of the total papers were published in 2018 [ 93 , 103 , 111 , 116 , 120 , 124 ], while 30.23% were published in 2019 [ 90 , 92 , 94 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary information of the included papers [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ] is shown in Table 1 . Based on the data shown in Figure 4 , we can observe that 13.95% of the total papers were published in 2018 [ 93 , 103 , 111 , 116 , 120 , 124 ], while 30.23% were published in 2019 [ 90 , 92 , 94 ,…”
Section: Resultsmentioning
confidence: 99%
“…However, many approaches that include blockchain technology in their designs are achieving promising results. Overall, 37.21% of the proposed schemes originate from China [ 92 , 94 , 95 , 96 , 97 , 102 , 104 , 105 , 113 , 114 , 119 , 124 , 125 , 128 , 129 , 132 ], and 62.79% are distributed between 14 countries [ 90 , 91 , 93 , 98 , 99 , 100 , 101 , 103 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 115 , 116 , 117 , 118 , 120 , 121 , 122 , 123 , 126 , 127 , 130 , 131 ]. Most of the included papers are published in journals, which result in 79.07% [ 90 , 91 , 94 , 96 , 97 , 98 , 99 , 100 , 102 , 104 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Developments in digital technologies in healthcare provide an opportunity to provide uninterrupted healthcare services. The use of digital healthcare systems has benefited monitoring, diagnosis, prevention, and treatment (7,8). Kapoor et al ( 9) demonstrated many digital applications useful for digital health purposes during the pandemic.…”
Section: Literature On Digital Technologies In Healthcarementioning
confidence: 99%